2022
DOI: 10.5534/wjmh.210001
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Metformin on Male Reproductive Function and Prostate: An Updated Review

Abstract: Metformin is the first-line oral antidiabetic drug that shows multiple pleiotropic effects of anti-inflamation, anti-cancer, anti-aging, anti-microbia, anti-atherosclerosis, and immune modulation. Metformin's effects on men's related health are reviewed here, focusing on reproductive health under subtitles of erectile dysfunction (ED), steroidogenesis and spermatogenesis; and on prostate-related health under subtitles of prostate specific antigen (PSA), prostatitis, benign prostate hyperplasia (BPH), and prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 147 publications
(194 reference statements)
1
24
0
Order By: Relevance
“…In small (and—apparently—underpowered) studies, the effects of MTF solely on men have been observed. This medication has been reported to be of benefit in non-diabetic men with erectile dysfunction who had not responded to sildenafil [ 75 ]. The mechanisms are obscure: they may be direct, via endothelium-dependent vasodilatation or attenuation of sympathetic nerve activity, and indirect, via MTF’s effect on blood pressure [ 75 ].…”
Section: Sex/gender Differences Using Mtfmentioning
confidence: 99%
“…In small (and—apparently—underpowered) studies, the effects of MTF solely on men have been observed. This medication has been reported to be of benefit in non-diabetic men with erectile dysfunction who had not responded to sildenafil [ 75 ]. The mechanisms are obscure: they may be direct, via endothelium-dependent vasodilatation or attenuation of sympathetic nerve activity, and indirect, via MTF’s effect on blood pressure [ 75 ].…”
Section: Sex/gender Differences Using Mtfmentioning
confidence: 99%
“…Given its nature as a glucose-lowering and anti-inflammatory drug [ 93 ], and that both high glucose and excessive inflammation cause male hypogonadism based on our studies [ 42 , 79 ], we would speculate that metformin could, at least to a certain extent, protect male diabetic patients from COVID-19-induced subfertility. However, various factors, including severity of diabetes, other complications such as obesity, hypertension and hyperlipidaemia, as well as dosage and duration of metformin treatment, which are reported to influence the effectiveness of metformin on male fertility in diabetic subjects [ 94 ], could complicate the unique circumstances in COVID-19.…”
Section: Covid-19-associated Diabetes Reduces Male Fertilitymentioning
confidence: 99%
“…However, longevity was extended by metformin administration only in Caenorhabditis elegans, reviewed by [195], and in only one of the tested strains of mice [196]. An extensive review by Tseng [197] summarized the effects of metformin on male reproductive health, specifically on erectile dysfunction, steroidogenesis, and spermatogenesis (showing beneficial effects on all issues, mostly in animal models). However, none of the studies were performed in aged animals or aged men.…”
Section: Nutrient-sensing Pathway Inhibitionmentioning
confidence: 99%